Small molecule therapeutics for neuroinflammation-mediated neurodegenerative disorders. Issue 6 (13th April 2021) - Miller, Silke; Blanco, Maria-Jesus
Abstract : Recent progress on key microglia targets and discovery of small molecule compounds advancing in clinical trials to minimize neuroinflammation. Abstract : Chronically activated microglia and the resulting cascade of neuroinflammatory mechanisms have been postulated to play a critical role in neurodegenerative disorders. Microglia are the main component of the brain's innate immune system and become activated by infection, injury, misfolded proteins or a multitude of other stimuli. Activated microglia release pro-inflammatory and cytotoxic factors that can damage neurons and transform astrocytes to become toxic to neurons as well. Therapeutic approaches aiming to modulate microglia activation may be beneficial to mitigate the progression of inflammatory-mediated neurodegenerative diseases. In this literature review, we provide an overview of recent progress on key microglia targets and discovery of small molecule compounds advancing in clinical trials to minimize neuroinflammation.